Sliding Wear Behavior of WP7V Tool Steel with Different Hardnesses Under Reciprocating Test Rig - Rogério Breganon; Francisco Arieta; Giuseppe Pintaude (Lubricants)
This study involved the investigation of the mechanical and tribological behaviors of DIN 1.2344 and WP7V tool steels, quenched in a salt bath after austenitization at 1050 °C, followed by triple tempering for 2 h. The selection of tempering temperatures produced two hardness levels under four metallurgical conditions, with the hardest level found only for WP7V steel (54 and 57 HRC). The mechanical properties were evaluated using Rockwell C, Vickers, and nanoindentation methods, along with unnotched impact tests, according to the SEP 1314 guidelines. Wear tests were conducted in a tribometer configured for a reciprocating setup, with a frequency of 5 Hz, a load of 25 N, and a time of 60 min, at room temperature and at 200 °C. As counterbodies, alumina balls of 5 mm in diameter were used. Wear tracks were evaluated through scanning electron microscopy, EDS, interferometry, and Raman spectroscopy. Friction and wear behaviors were affected by the variation in temperature for softer steels (DIN 1.2344 and WP7V of 48.5 HRC): the higher the temperature, the better the tribological performance. The harder steels were not sensitive to temperature testing. These effects depend on maintaining iron oxide (hematite) at the point of contact. The wear rates determined for the hardest material (57 HRC), considering its impact resistance, make it unsuitable for severe conditions such as hot stamping.